Temperature-controlled transparent-film heater based on silver nanowire–PMMA composite film. (26th October 2016) - He, Xin; Liu, A'lei; Hu, Xuyang; Song, Mingxia; Duan, Feng; Lan, Qiuming; Xiao, Jundong; Liu, Junyan; Zhang, Mei; Chen, Yeqing; Zeng, Qingguang
Abstract: We fabricated a high-performance film heater based on a silver nanowire and polymethyl methacrylate (Ag NW–PMMA) composite film, which was synthesized with the assistance of mechanical lamination and an in situ transfer method. The films exhibit excellent conductivity, high figure of merit, and strong adhesion of percolation network to substrate. By controlling NW density, we prepared the films with a transmittance of 44.9–85.0% at 550 nm and a sheet resistance of 0.13–1.40 Ω sq −1 . A stable temperature ranging from 130 °C–40 °C was generated at 3.0 V within 10–30 s, indicating that the resulting film heaters show a rapid thermal response, low driving voltage and stable temperature recoverability. Furthermore, we demonstrated the applications of the film heater in defrosting and a physical therapeutic instrument. A fast defrosting on the composite film with a transmittance of 88% was observed by applying a 9 V driving voltage for 20 s. Meanwhile, we developed a physical therapeutic instrument with two modes of thermotherapy and electronic-pulse massage by using the composite films as two electrodes, greatly decreasing the weight and power consumption compared to a traditional instrument. Therefore, Ag NW–PMMA film can be a promising candidate for diversified heating applications.